Contribution of Muslim scientists to the world: an overview of some selected fields - Afridi, Muhammad Adil Khan (2011)
Islam has its own golden history almost in every sectors of knowledge. The main theological doctrine of Islam, Al Quran also gives the utmost emphasize on pursuing knowledge. Muslim scholars from the past were very much aware of this instruction given by Allah s.w.t and they were very much captivated onto that. They developed many ideas and theories in the field of knowledge. This paper will try to shed a light on few works that have been carried out by the Muslim scholars. However, it focuses on the contributions of Muslim scholars in Mathematics, Physics and Medicine only. This paper will also promote Islamization of Knowledge and its necessity for solving current Muslim world’s educational problems. It is also hoped that, by remembering all those Muslim heroes and their contributions, contemporary Muslim societies, scholars will be inspired.